Implementation of Policies for the Empowerment of the Suku Anak Dalam (SAD) in vercoming the Nomadic Culture in the Province of Jambi (Analysis of Livelihood Assets) - Isyaturriyadhah Isyaturriyadhah; Yonariza Yonariza; Erwin Erwin; Mahdi Mahdi (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
The objectives of this study are to examine the implementation of government policies on the empowerment program of Suku Anak Dalam (SAD) related to livelihood assets and to describe the performance of SAD assets in Jambi Province. The study was conducted in 2024. The study location was determined purposively in Dwi Karya Bhakti Village, Pelepat District, Bungo Regency, and Muara Kilis Village, Tebo Tengah District, Tebo Regency, considering that these locations had received various empowerment programs and obtained agricultural land for the SAD community. Respondents were identified through the census, specifically 93 SAD individuals who had been empowered. They were then interviewed, along with the Head of the Service/Secretary of the Food Crops, Horticulture, and Plantation Service of Bungo Regency and Tebo Regency, as well as Tumenggung and SAD Companion Figures. This study used a descriptive analytical approach to describe the implementation of government policies. The livelihood assets were scored using indicators of natural capital, financial capital, social capital, human capital, and physical capital. The research findings indicate that there are no regulations or policies from the Jambi Provincial Regulation regarding SAD assistance, specifically in the agricultural sector, in Bungo and Tebo Regencies. Based on livelihood assets, it is known that the livelihood assets of SAD are not yet optimal. This study highlights the need for maximum assistance that focuses on livelihood assets so that the level of nomadic people in SAD can be overcome and the success of the program, especially in the agricultural sector, can be achieved.